Helicobacter Pylori Infection in Endoscopic Biopsy Specimens of Gastric Cancer: A Preliminary Evaluation in a High Risk Population of Kashmir Valley. Issue 1 (1997) - Malik, G. M.; Kadla, S.; Mubarik, M.; Hussain, T.; Jeelani, G.; Basu, J.; Rashid, S.; Ahmad, M.; Nafee, A.; Khan, A. R.
Abstract : Objective : The aim of the present study was to assess the prevalence of Helicobacter pylori (H. pylori) infection in Kashmiri patients with gastric cancer and to compare this with a matched control population. Methods : Fifty patients with gastric cancer and thirty age/sex matched controls were included in the study. All the subjects were hailing from Kashmir Valley. For detection of H. pylori, biopsy specimens were used both from cases and controls. Results : An insignificant association was shown between H. pylori and both intestinal and diffuse type of gastric cancer. Conclusions : The data provides support against the significant association between H. pylori and gastric cancer in this part of world, a place where the age standardized incidence of gastric cancer is alarmingly high. We conclude that other factors like personal and special dietary habits of Kashmiri population may be more important for the development of gastric cancer.